Pengaruh Perlakuan Ethyl Methane Sulfonate pada Tanaman Cabai (Capsicum annuum L.) dan Ketahanannya terhadap Chilli Veinal Mottle Virus (ChiVMV) - Ifa Manzila; Sri Hendrastuti Hidayat; Ika Mariska; Sriani Sujiprihati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
Ethyl Methane Sulfonate (EMS) may induce mutation leading to somaclonal variation if it is used at the appropriate combination of EMS concentration and exposure time. Variation in somaclonal might be valuable as a source of resistance to plant pathogens including plant viruses. This study was aimed 1) to determine the optimum EMS concentration and incubation time that may induce somaclonal variation in chilli pepper; and 2) to evaluate the resistance of the somaclone to ChiVMV infection. Shoot-tip explants of fi ve chilli pepper genotypes (Jatilaba, ICPN 12#4, PBC495, Helem, and Gelora) were treated with EMS at combination of different concentrations (0.25%, 0.5% 1.0% and control), and incubation time (15, 30, 60 min). Subsequently, each explant was grown in multiplication media (MS media + 5 mg L -1 BAP + 0.5 mg L-1 TDZ), rooting media (MS media + 1 mg L-1 NAA), and acclimatization media (mixture of soil : sand : compost 2:1:1 w/w). Our results showed that the higher EMS concentration and the longer incubation period the smaller the number of survive explants. The highest survival rate 20.4 % was achieved with 0.5% EMS in combination with 60 min incubation period. This treatment combination also showed induction of phenotypic variation. Two somaclonal plants derived from Gelora genotype, designated as somaclones K1 and K2, survived until fruit development and maturation. A total of 245 progenies of K1 and 243 progenies of K2, respectively were evaluated for their resistance to ChiVMV infection through mechanical inoculation using ChiVMV-Cikabayan isolate. Following the detection of ChiVMV using DAS-ELISA, it was confi rmed that 4.09% of the somaclonal progenies were resistance to ChiVMV. Keywords: Capsicum annuum L., ChiVMV, ethyl methane sulfonate, induce mutation, resistance